Mechano-responsive room temperature luminescence variations of boron conjugated pyrene in air - Wakchaure, Vivek C.; Ranjeesh, Kayaramkodath C.; Goudappagouda; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh; Babu, Sukumaran S. (Chemical Communications, 2018)
Stimuli responsive tunable luminescence is a promising field of research. Even though mechanofluorescence is widely studied, mechanophosphorescence remains unexplored. Here we report the mechano-driven fluorescence and phosphorescence variations of a pyrene tetraboronic ester derivative. The fluorochromic and room temperature phosphorescence features are supported by theoretical studies and single crystal analysis. The mechanically ground fluorescence active but phosphorescence inactive pyrene tetraboronic ester exhibits room temperature phosphorescence in air withmechanical force. The efficient intermolecular electronic coupling in the dimer formed upon scratching enables a good communication between singlet and triplet states, hence resulting in room temperature mechanophosphorescence.

Hexaaminobenzene derived two-dimensional polymer supercapacitor with high specific capacitance and energy density - Wakchaure, Vivek C.; Kottaichamy, Alagar R.; Nidhankar, Aakash D.; Ranjeesh, Kayaramkodath C.; Nazrulla, Mohammed A.; Thotiyl, Musthafa O.; Babu, Sukumaran S. (ACS Applied Energy Materials, 2020)
Recent research interest has been shifted toward energy storage devices, especially supercapacitors, which provide high specific power and long cycle life. In this context, two-dimensional organic polymers are a class of versatile materials found to be useful in energy storage applications. However, the performance is not promising due to the low capacitance, energy density, and cyclic stability. Here, we report a two-dimensional polymer derived from hexaaminobenzene and pyromellitic dianhydride and its excellent supercapacitor performance. The specific capacitance of the two-dimensional polymer is found to be 805 F g(-1) at 0.5 A g(-1) current density in galvanostatic charge-discharge, which is the highest among the organic twodimensional polymer and most of the carbon-based materials. The superior performance of the 2D-polymer compared to a model derivative (350 F g(-1) at 0.5 A g(-1) current density) points to the critical role of a 2D-platform to excel. The high energy density, excellent cyclic stability, and low self-discharge rate support the 2D-polymer supercapacitor as a promising candidate for futuristic applications.
Keywords: 2D-polymer; energy density; Energy storage; hexaaminobenzene; supercapacitor